One-year grazing exclusion remarkably restores degraded alpine meadow at Zoige, eastern Tibetan Plateau - Miao Liu; Zhenchao Zhang; Jian Sun; Yi Wang; Jinniu Wang; Atsushi Tsunekawa; Mesenbet Yibeltal; Ming Xu; Youjun Chen (Global Ecology and Conservation, 2020)
Understanding the influences of grazing exclusion (GE) on soil properties and vegetation characteristics is essential for the assessment of grassland restoration. The objectives of this study are exploring the efficiency of short-term GE in restoring alpine meadow in the Zoige region, eastern Tibetan Plateau, with high rainfall amount. We conducted sampling surveys before and after one-year GE in alpine meadows with seven sequent degraded degrees. The results showed that one-year GE significantly increased soil organic carbon (SOC), soil total nitrogen (STN), soil water content (SWC), and plant biomass, while decreased soil bulk density (SBD) regardless of the degradation degree. These findings suggest that short-term GE may be an effective way to restore degraded alpine meadow. Aboveground and belowground biomass was significantly positively associated with SWC, SOC, STN, soil total phosphorus, and soil available nitrogen, but presented negative relationship with SBD. This shows the complicated interaction between vegetation and soil physiochemical properties that regulates the grassland recovery process. The degraded alpine meadow in this rainfall-rich region could rapidly recover once grazing disturbance was excluded. This study can provide technical support for restoration and sustainable management of alpine meadows on the Tibetan Plateau.